2015
DOI: 10.1155/2015/564095
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Mechanism of Low-Frequency rTMS on Nigral Dopaminergic Neurons of Parkinson’s Disease Model Mice

Abstract: Background. Parkinson's disease is a neurodegenerative disease in elder people, pathophysiologic basis of which is the severe deficiency of dopamine in the striatum. The purpose of the present study was to evaluate the neuroprotective effect of low-frequency rTMS on Parkinson's disease in model mice. Methods. The effects of low-frequency rTMS on the motor function, cortex excitability, neurochemistry, and neurohistopathology of MPTP-induced Parkinson's disease mice were investigated through behavioral detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…While anti-inflammatory activity via paracrine factors appears to be a key to the therapeutic benefits of MSCs [74,75], the molecular mechanisms underlying the therapeutic effects of rTMS remain unclear. The safety and efficacy of long-term rTMS was demonstrated in a number of experimental models and clinical studies for PD [76][77][78][79][80][81]. The present study revealed that rTMS and transplanted hMSCs modulated various neurotrophic growth factors, and that BDNF, GDNF, NGF, NGF and PDGF-AA expression levels were increased by the rTMS and hMSC treatments in PD rats.…”
Section: Changes In Pro-/anti-inflammatory Cytokine Expression Upon Rtms Treatment And/or Hmsc Transplantationsupporting
confidence: 55%
“…While anti-inflammatory activity via paracrine factors appears to be a key to the therapeutic benefits of MSCs [74,75], the molecular mechanisms underlying the therapeutic effects of rTMS remain unclear. The safety and efficacy of long-term rTMS was demonstrated in a number of experimental models and clinical studies for PD [76][77][78][79][80][81]. The present study revealed that rTMS and transplanted hMSCs modulated various neurotrophic growth factors, and that BDNF, GDNF, NGF, NGF and PDGF-AA expression levels were increased by the rTMS and hMSC treatments in PD rats.…”
Section: Changes In Pro-/anti-inflammatory Cytokine Expression Upon Rtms Treatment And/or Hmsc Transplantationsupporting
confidence: 55%
“…It is reported that the degeneration of nigral dopaminergic neuron is due to the lack of trophic support. 29 So far, the importance of neurotrophic factors such as BDNF and GDNF upon PD progression has attracted more attention. 30 Besides the trophic role, BDNF and GDNF are potent promoters responsible for neuronal survival in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…These structures render the plasma membrane and the mechanically sensitive ion channels present in them highly susceptible to external MF which alters the permeability of membranes and ion channels, thereby modulating the secretion and synthesis of various neurotransmitters and metabolites. 36,37 A greater sparing of dopaminergic terminals after MF exposure (31%) as compared to PD was observed. This could be because of the reduction in oxidative stress, inflammation, or release of neurotrophic factors.…”
Section: Discussionmentioning
confidence: 91%